Konstruksi Mobile Journalism dalam Praktik Komunikasi Resiko dan Pemberdayaan Masyarakat di Era Pandemi Covid-19 - I Made Puja Artana; Ni Luh Senja Harining; Ni Nyoman Puji Artini; I Ketut Putu Suardana (Program Studi Magister S2 Ilmu Komunikasi Hindu Institut Agama Hindu Negeri Gde Pudja Mataram, 2021)
Mobile journalism is the result of the transformation of traditional journalism into online journalism by utilizing mobile phone technology. Meanwhile, the practice of risk communication and community empowerment (KRPM) in the Covid-19 era is an effort to prevent the spread of infodemic in the form of fake news / hoaxes in the Corona Virus Desiase 2019 (Covid-19) era. Thus, this article examines the construction of mobile journalism in KRPM practice in the Covid-19 era. The data of this article was obtained through a search using the literature review method, which is a research method that describes and critically assesses something that is already known about a topic using secondary sources. Scientific works whose studies are related to this topic are explored and elaborated in depth. Based on a literature review, mobile journalism is a form of online journalism that plays a significant role in the practice of KRPM in the Covid-19 era. The use of mobile phone technology in KRPM practice in the Covid-19 era is so great that constructing mobile journalism is one of the primary needs when preventing infodemic in the form of fake news/hoaxes by stakeholders in charge of preventing the spread of Covid-19. On the other hand, the ease of mobile journalism is misused by unscrupulous spreaders of fake news. Thus, it is recommended for the wider community to verify information about Covid-19 on mobile journalism activities from sources or official accounts of the Task Force for the Acceleration of Handling Corona Virus Disease 2019 (Covid-19).